Software engineering and formal methods : 13th International Conference, SEFM 2015, York, UK, September 7-11, 2015. Proceedings /: 13th International Conference, SEFM 2015, York, UK, September 7-11, 2015. Proceedings. (2015) - Unknown
No abstract available